Education on Hybrid Multi-Criteria Decision Making and Machine Learning through the Morning Class Program: Integration of Engineering and Technology - Nasir Usman; Muhammad Faisal; Sri Wahyuni; Saharuddin Saharuddin; Lisa Fitriani Ishak; Darniati Darniati; Musdalifa Thamrin; Emil Agusalim Habi Talib; Alvina Felicia Watratan (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2026)
The Society 5.0 era requires mastery of transparent and intelligent decision systems, yet practical understanding of integrating Machine Learning (ML) and Multi-Criteria Decision Making (MCDM) through Hybrid Intelligence frameworks remains limited in academic environments. This community service aims to enhance the scientific capacity of academics through the